Years of change - Gibb, Hugh. ([Manila] Felta Book Sales [distributor], 1981)
Outlines and characterizes the major periods in Philippine history from the years of Spanish sovereignty to the years of martial law. Cites the constancy of Filipino idealism throughout these changes.
Keywords: Philippines -- History